A bond with a child during pregnancy and the self-efficacy of mothers - Martyna Maciejewska; Inga Janik-Fuks; Agnieszka Wilczyńska; Agata Wawryków; Monika Stecko; Anna Fabian-Danielewska; Katarzyna Korabiusz (Kazimierz Wielki University, 2019)
The basic direction of monitoring and analyzing the process of procreation, getting pregnant, its course, possible complications and delivery is a medical, biological perspective. Psychology has entered medical areas practically with all its basic research directions. Many publications from the fringe of psychology and obstetrics draw attention to the magnitude of possible factors affecting the quality of the relationship of the mother and her newborn child. Preliminary conclusions were based on a pilot study - it included 43 pregnant women. The study was conducted among patients in hospitals, specialist counseling centers and gynecological surgeries, and clients of birthing class. The respondents filled out the following questionnaires: Author's sociometric-medical survey, Maternal Fetal Attachment Scale (Cranley); General Self-Efficacy Scale (Schwarzerer and Jerusalem). Statistical analysis (Pearson correlation coefficient) of selected variables showed statistically insignificant (p> 0.05) correlations from very weak to high. A high correlation occurs between the week of pregnancy and a sense of bond with the child (r = 0.792) and a week of pregnancy and a sense of self-generalized effectiveness (r = 0.847).